The combined effects of exercise and food intake on adipose tissue and splanchnic metabolism - Enevoldsen, L H (Blackwell Science Inc, 2004)
Seven young, healthy male subjects were each studied in two separate experiments. (1) Subjects exercised for 60 min at 55% of peak oxygen consumption in the fasted state ending 30 min before a meal (60% of energy as carbohydrate, and 20% of energy as lipid and protein each) comprising 25% of the total daily energy intake, and were then studied for another 150 min postprandially during rest (E→M). (2) One hour after a similar meal, subjects exercised for 60 min and were then studied for another 180 min postexercise during rest (M→E). Regional adipose tissue and splanchnic tissue metabolism were measured by Fick's Principle. Food intake before exercise reduced whole-body lipid combustion during exercise to about 50% of the combustion rate found during exercise in the fasted state. The increase in subcutaneous, abdominal adipose tissue lipolysis during exercise was not influenced by preexercise food intake, while the fatty acid mobilization was increased by only 1.5-fold during postprandial exercise compared to a fourfold increase during exercise in the fasted state. During exercise, catecholamine concentrations increased similarly in the fasted and the postprandial state, while the insulin concentration was twofold higher postprandially. These results indicate that the increase in catecholamine concentrations during exercise is a more important determinant of the adipose tissue lipolytic rate than the decrease in insulin concentration. Furthermore, food intake either 30 min after or 1 h before exercise prevents the postexercise increase in adipose tissue glycerol and fatty acid release which normally takes place in fasting subjects at least up to 2.5 h postprandially. Postprandial exercise led to a faster increase in postprandial lipaemia. This could not be accounted for by changes in the regional splanchnic tissue or adipose tissue triacylglycerol metabolism. Exercise was able to increase hepatic glucose production irrespective of food intake before exercise. It is concluded that exercise performed in the fasted state shortly before a meal leads to a more favourable lipid metabolism during and after exercise than exercise performed shortly after a meal.